Caring and Criminalising - Lingis, Alphonso (Critical Studies in Teaching and Learning, 2023)
In the United States, many schools hire police to patrol the grounds and more call upon police to arrest students for violation of school policies. Many of these will be incarcerated within the subsequent five years. The widespread adoption of surveillance cameras, zero tolerance, and police presence in schools has resulted in more students being criminalised. This reflective essay examines the ideology supporting this school-to-prison pipeline. What conception of justice has been responsible for mass incarceration? Why are surveillance cameras, police, and zero toler- ance taken to be effective? Why has rehabilitation given way to retribution? Why does the public accept the criminalisation of youth in schools?